Sequence and comparative analysis of the chicken genome provide unique perspectives on vertebrate evolution. [Erratum: 2005 Feb. 17, v. 433, no. 7027, p. 777.] - Hillier, L.W.; Miller, W.; Birney, E.; Warren, Wesley; Hardison, R.C.; Ponting, C.P.; Bork, Peer; Burt, D.W.; Groenen, M.A.M.; Delany, M.E.; Dodgson, J.B.; Chinwalla, A.T.; et al. (Nature (London), 2004)
We present here a draft genome sequence of the red jungle fowl, Gallus gallus. Because the chicken is a modern descendant of the dinosaurs and the first non-mammalian amniote to have its genome sequenced, the draft sequence of its genomecomposed of approximately one billion base pairs of sequence and an estimated 20,000-23,000 genes-provides a new perspective on vertebrate genome evolution, while also improving the annotation of mammalian genomes. For example, the evolutionary distance between chicken and human provides high specificity in detecting functional elements, both non-coding and coding. Notably, many conserved non-coding sequences are far from genes and cannot be assigned to defined functional classes. In coding regions the evolutionary dynamics of protein domains and orthologous groups illustrate processes that distinguish the lineages leading to birds and mammals. The distinctive properties of avian microchromosomes, together with the inferred patterns of conserved synteny, provide additional insights into vertebrate chromosome architecture.